Utilizing Sugarcane Wasted Fibers As A Sustainable Acoustic Absorber - Putra, Azma (ELSEVIER, 2013)
The use of synthetic materials as acoustic absorbers is still applied extensively in building industry. These non- biodegradable materials do not only cause pollution to the environment, but their production also contributes significantly in emitting green house gas in the atmosphere. Corresponding research has therefore being driven to find sustainable and eco- friendly materials to be an alternative sound absorber. This paper discusses the utilization of natural fibers from sugarcane waste to be an acoustic material. Sound absorber samples from sugarcane wasted fibers are fabricated and their acoustic properties are investigated through experiment. Good acoustic performance is found at 1.2 - 4.5 kHz with average absorption coefficient of 0.65 and is comparable against that from the classical synthetic absorber.